Ecological and geochemical state of soils and grounds of Moscow green spaces (analytical review) - T. I. Borisochkina; B. M. Kogut; Sh. A. Khamatnurov (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The paper assesses the pollution of soils and grounds of green spaces in Moscow with heavy metals and de-icing agents. The analysis of literature sources indicates a decrease in integral pollution index of soils and grounds of green spaces in the city in recent years. The decrease in the integral pollution index is determined by the reduction of emissions from industrial enterprises and by the land reclamation with the replacement of the upper soil layer. At the same time, an observed increase in the lead concentrations in urban landscapes was caused by intensive automobile traffic. The lack of green territories was noted in central part of the metropolis, which is below the norm recommended by WHO (50 m2 of tree plantations per person). The processes of soil salinization and suppression of urban vegetation caused by the use of de-icing reagents are described. The literature data on the anthropogenic transformation of physical and chemical properties of soils and forms of heavy metal compounds in soils are presented. It is indicated that the study of these issues is promising for solving ecological-hygienic problems of the megalopolis. Soils of green spaces in Moscow are proposed to be divided into three groups, taking into account the genesis, ecological and geochemical state: 1) soils on artificial bulk ground of designed landscapes, 2) transformed soils with traces of past anthropogenic impact (postagrogenic soils, soils of post-settlement territories, 3) soils on the territories of parks, forest parks and forests, slightly affected by human activities and retaining the properties of natural zonal soils.